2021
DOI: 10.1071/ah20289
|View full text |Cite
|
Sign up to set email alerts
|

Are we doing it right? We need to evaluate the current approaches for implementation of digital health systems

Abstract: Successful implementation of digital health programs is imperative as it is becoming increasingly clear that digital solutions will underpin modern health care. These projects are often supported by large budgets and if not implemented successfully, the quality, safety, and efficiency of patient care may be compromised. Failure rates for the implementation of large, complex healthcare software platforms in digital health programs have been persistently high. Although several factors may contribute to the failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…An article by Dendere (Dendere et al, 2021) , citing media reports and professional literature, finds a global trend of failed healthcare projects related to digital transformation. The main cause is supposed to be project management, more precisely the choice of a suitable project management approach ("Adopting a suitable project management approach is a major factor for achieving success because managing a project using an unsuitable methodology can severely damage the chances of success.").…”
Section: Discussionmentioning
confidence: 99%
“…An article by Dendere (Dendere et al, 2021) , citing media reports and professional literature, finds a global trend of failed healthcare projects related to digital transformation. The main cause is supposed to be project management, more precisely the choice of a suitable project management approach ("Adopting a suitable project management approach is a major factor for achieving success because managing a project using an unsuitable methodology can severely damage the chances of success.").…”
Section: Discussionmentioning
confidence: 99%
“…Članek Dendere (Dendere et al, 2021), ki se sklicuje na zapise v medijih in strokovno literaturo, navaja globalni trend neuspešnih projektov v zdravstvu, povezanih z digitalno transformacijo. Glavni vzrok naj bi bilo vodenje projektov, bolj natančno: izbira primernega pristopa za vodenje projekta (»Adopting a suitable project management approach is a major factor for achieving success because managing a project using an unsuitable methodology can severely damage the chances of success.«).…”
Section: Uvodunclassified
“…For instance, Naik et al (2022) discuss how digital health technologies can be leveraged to combat pandemic urgency, and synthesizes challenges and opportunities associated with technology adoption. Dendere et al (2021) evaluated the different approaches adopted by countries for the implementation of digital health solutions. A study also identified the factors influencing elderly adults experience with digital health technologies and proposed a research design strategy for future researchers as well (Farhanum et al, 2021).…”
Section: Introductionmentioning
confidence: 99%